2011
DOI: 10.4085/1062-6050-46.3.230
|View full text |Cite
|
Sign up to set email alerts
|

Increased QT Interval Variability in 3 Recently Concussed Athletes: An Exploratory Observation

Abstract: Context:The QT interval variability index (QTVI) is a noninvasive measure of beat-to-beat fluctuations of the QT interval as seen from a single electrocardiographic lead. It represents the relationship between the respective variabilities of the QT and R-R intervals. Recently, the QTVI was demonstrated to be an index of vagal cardiac autonomic modulation in resting conditions.Objective: To determine whether QTVI varied in athletes at 48 hours, 1 week, and 2 weeks after a concussive head injury.Design: Case ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…This study allowed us to directly observe the influence of concussion on regulation of the cardiac rhythm in symptomatic athletes. Comparable research has limited the evaluation of regulatory dysfunction to patients already asymptomatic [5,6], during isometric exercise [10] or while the individual is at rest [13]. In addition, while other studies have explored the capacity of the autonomic system to adjust and respond to prolonged steady-state exercise, our study specifically evaluated the anticipatory response to exercise and adjustment to a change in exertion level over time, which is more representative of athletic performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study allowed us to directly observe the influence of concussion on regulation of the cardiac rhythm in symptomatic athletes. Comparable research has limited the evaluation of regulatory dysfunction to patients already asymptomatic [5,6], during isometric exercise [10] or while the individual is at rest [13]. In addition, while other studies have explored the capacity of the autonomic system to adjust and respond to prolonged steady-state exercise, our study specifically evaluated the anticipatory response to exercise and adjustment to a change in exertion level over time, which is more representative of athletic performance.…”
Section: Discussionmentioning
confidence: 99%
“…La Fountaine et al [10] demonstrated that autonomic activity at rest could differentiate concussed from non-concussed controls and that vagal dysfunction after concussion resulted in an increase in vagal activity at 48 hours post-injury despite evidence for sympathetic hyperactivity one week and two weeks later [13]. Similarly, an animal model of brain injury showed a significantly lower resting HR in concussed rats on the day of injury when compared with sham-treated rats [7], suggesting that the nature of autonomic system dysfunction after injury is time dependent, with vagal dysfunction from a state of sluggish withdrawal to one of disordered engagement or re-engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Autonomic tests may be effective in identifying concussion or PCS. La Fountaine et al 27,28 showed that 2 measures of cardiac vagal modulation, the QT interval variability index at rest and HR complexity during isometric hand-grip exercise, were altered within 48 hours of head injury, resolved within 1 week, and remained at control levels 2 weeks later, consistent with vagal dysfunction early after concussion. In a controlled study of HRV in university athletes who were judged to be clinically recovered from concussion (a mean of 95 days postinjury), Abaji et al 50 found that during the isometric hand-grip exercise, but not at rest, athletes with a history of concussion had less HF power and a greater LF : HF ratio than age-and teammatched controls with no history of concussion.…”
Section: The Physiology Of Concussionmentioning
confidence: 93%
“…Concussion affects the autonomic nervous system (ANS) 27,28 and the control of both cerebral blood flow (CBF) [29][30][31][32] and cardiac rhythm. 33,34 The primary ANS control center may be damaged in concussion, particularly if a rotational force was applied to the upper cervical spine, 35 as supported by results from a diffusion tensor imaging study 36 that showed changes to brainstem white matter neurons after concussion.…”
Section: The Physiology Of Concussionmentioning
confidence: 99%